Patterns of Facial Bone Fractures in Western Region of Nepal - Bhatta, Rishi; Pyakurel, Manita; Prabhu, Namdeo; Kansakar, Niva (Nepalese Journal of ENT Head and Neck Surgery, 2018)
Objective: The aim of this study was to determine pattern of facial bones fracture in western region of Nepal. Material and Methods: A descriptive cross sectional study was carried out in department of ENT, Nepalgunj medical college, Nepalgunj. Records from emergency department, inpatient ward and OPD of ENT and dental department of last 3 years (Jan 2012 to Dec 2014) were enrolled in the study and entered into proforma. Comparison was done between mode of injury, demography and types of injuries. Data was analyzed using SPSS 17 software. Results: Out of included 626 cases, there were 410 male patients and 216 female patients. Age ranged from 3 to 68 years with average age being 32.4 years. Most of the male patients sustained trauma due to road traffic accidents (51.7%) followed by physical assault (23.9%). In female also same mode of injuries were common with higher proportion due to physical assault. Majority of cases were from Midwestern Terai region (35.4%). There were 288(46.0%) cases with isolated facial bone fracture. The maximum was that of mandibular fracture (29.1%) followed by nasal bone fracture (27.7%) and maxilla (24.3%). Rest of 338 patients had multiple facial bone fractures with zygomatic bone fracture (79.2%) being commonest. It was followed by maxilla (64.4%) and mandible fracture (36.6%). The overall frequency of fracture is mainly involving zygomatic bone (49.5%) followed by maxilla (46.0%) and mandible (33.2%). Conclusion: Middle aged male patients are usually involved in facial bone fractures with road traffic accident and physical assault being common modes of injury. Zygomatic bone is the commonest bone to get fractured in isolated cases while mandible is commonest bone to get fractured in multiple fracture cases. Nepalese Journal of ENT Head and Neck Surgery, Vol. 6, No. 1, 2015